Exports of the Kurds during the Abbasid Period (961-1055) - Omer, Ardalan Ismail (Journal of Duhok University, 2019)
The exports form one of the main elements of business that economic relations are built on it where Kurdish authorities in regions that Kurds were in with Islamic forces, and due to the many good things in the area especially in agricultural site, during the Abbasid period these areas had attracted a great deal of interest in the ancient sources especially the sources between the two areas. This may be due to the flourishing trade movement of that era and the rapid development of social and economic life. The region of the Kurds enjoyed abundant agricultural and industrial crops that increased the production of the needs of its population, so it was common that the ruling authorities were concerned with the disposal of the surplus of these products and crops abroad, especially to Iraq.